1998
DOI: 10.1111/j.1440-1819.1998.tb01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep using ambulatory skin potential recording:Differences between morning and evening type

Abstract: In order to validate the evaluation of sleep using cassette type ambulatory skin potential measurement system (C-SPA), sleep duration variables extracted from 24 h recordings were compared between two groups (16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
5
4
0
Order By: Relevance
“…Recently, Barclay et al . demonstrated that eveningness is associated with poor sleep quality, which is consistent with previous suggestions, 31–35 remarking that it may be related to intrinsic properties of the circadian system. These findings support our results that evening types have significantly poorer subjective sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Barclay et al . demonstrated that eveningness is associated with poor sleep quality, which is consistent with previous suggestions, 31–35 remarking that it may be related to intrinsic properties of the circadian system. These findings support our results that evening types have significantly poorer subjective sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…We reported previously our observation of intermittently recorded SP in a case of delirium 2 . In the present study, we were able to observe a 1‐week record of SP fluctuations, in which the process of degenerating sleep–wake cycle was clearly shown.…”
Section: Discussionsupporting
confidence: 69%
“…We reported previously our observation of intermittently recorded SP in a case of delirium. 2 In the present study, we were able to observe a 1-week record of SP fluctuations, in which the process of degenerating sleep-wake cycle was clearly shown. It was also interesting to note that there was a period of relatively high SP level without excitement before the delirium finally appeared.…”
Section: Discussionsupporting
confidence: 56%
“…Our finding that evening type subjects report poorer sleep quality is also documented in a study using cassette‐type ambulatory skin potential measurement system. It showed that the evening type subjects awakened during sleep more frequently than the morning type (Shiihara et al. , 1998).…”
Section: Discussionmentioning
confidence: 99%